PENGARUH KOMUNIKASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT BUMI AGUNG WILAYAH KOTA TANGERANG SELATAN - M. Anton Nurhidayat (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to determine the effect of communication and work stress on the performance of employees of PT. Bumi Agung area of ??South Tangerang City, either partially or simultaneously. The method used is descriptive quantitative. The sampling technique was incidental and obtained a sample of 160 respondents. Data analysis used validity test, reliability test, classical assumption test, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the results of the t-test calculation, the t-value of the Communication variable is 14,892 with a significance of 0.000 <0.05, while the t-table is 1.975. Then obtained t count > t table (14,892 > 1,975). This means that the communication variable partially affects employee performance. The t value of the Work Stress variable is 5.284 with a significance of 0.000 <0.05, while the t table is 1.975. Then obtained t arithmetic > t table (5.284 < 1.975). This means that the work stress variable partially affects employee performance. The results of the F test obtained the Fcount 114.508 > Ftable 3.05 with a significant 0.000 < 0.05 or (Fcount > Ftable) and a significant 0.000 < 0.05. So that it can be concluded that simultaneously Communication and Work Stress together affect employee performance. The multiple linear regression equation obtained is Y = 14,434 + 0,544 X1 + 096 X2. The R value is 0.770 or 77%, which means that the correlation between Communication and Work Stress on Employee Performance is in the strong category (0.600-0.799), with a coefficient of determination of 0.593. This shows that 59.3% of communication and work stress simultaneously affect employee performance, while the remaining 40.7% is influenced by other factors.